ELTD1 activation induces an endothelial-EMT transition to a myofibroblast phenotype - Sheldon, H; Alexander, J; Bridges, E; Moreira, L; Reilly, S; Ang, KH; Wang, D; Lin, S; Haider, S; Banham, AH; Harris, AL (MDPI, 2021)
ELTD1 is expressed in endothelial and vascular smooth muscle cells and has a role in angiogenesis. It has been classified as an adhesion GPCR, but as yet, no ligand has been identified and its function remains unknown. To establish its role, ELTD1 was overexpressed in endothelial cells. Expression and consequently ligand independent activation of ELTD1 results in endothelial-mesenchymal transistion (EndMT) with a loss of cell-cell contact, formation of stress fibres and mature focal adhesions and an increased expression of smooth muscle actin. The effect was pro-angiogenic, increasing Matrigel network formation and endothelial sprouting. RNA-Seq analysis after the cells had undergone EndMT revealed large increases in chemokines and cytokines involved in regulating immune response. Gene set enrichment analysis of the data identified a number of pathways involved in myofibroblast biology suggesting that the endothelial cells had undergone a type II EMT. This type of EMT is involved in wound repair and is closely associated with inflammation implicating ELTD1 in these processes.